25.6k views
1 vote
9 - 4(2p - 1) = 41 Show work

2 Answers

1 vote

Answer:


p=-(7)/(2)

Explanation:


9 - 4(2p - 1) = 41 \\\\\mathrm{Subtract\:}9\mathrm{\:from\:both\:sides}\\9-4\left(2p-1\right)-9=41-9\\\\Simplify\\-4\left(2p-1\right)=32\\\\\mathrm{Divide\:both\:sides\:by\:}-4\\(-4\left(2p-1\right))/(-4)=(32)/(-4)\\\\Simplify\\2p-1=-8\\\\\mathrm{Add\:}1\mathrm{\:to\:both\:sides}\\2p-1+1=-8+1\\\\Simplify\\2p=-7\\\\\mathrm{Divide\:both\:sides\:by\:}2\\(2p)/(2)=(-7)/(2)\\\\Simplify\\p=-(7)/(2)

User Darryl Noakes
by
5.1k points
6 votes

Answer:


p=-7/2=-3.5

Explanation:

So we have the equation:


9-4(2p-1)=41

First, let's subtract 9 from both sides:


-4(2p-1)=32

Divide both sides by -4:


2p-1=-8

Add 1 to both sides:


2p=-7

Divide both sides by 2:


p=-7/2=-3.5

And we're done!

User David Oliver
by
5.5k points